The size exclusion chromatography calibration of 'Mixed-A' and 'Mixed-D' columns using various polymers and compounds: An application to coal-derived materials - Karaca, F; Millan, M; Behrouzi, M; Herod, AA; Kandiyoti, R (ELSEVIER, 2005)
This work attempts to obtain the calibration curves of two different size exclusion chromatography (SEC) columns operating with 1-methyl-2-pyrrolidinone (NMP) as eluent by using various standards. Polystyrene (PS) and polymethylmethacrylate (PMMA) standards were used for obtaining calibration curves, and checked against polysaccharide (PSAC) standards, some small aromatic polycyclic standards and miscellaneous polymers. Polystyrenes and polymethylmethacrylates gave identical calibrations while polysaccharides and miscellaneous polymers lay within 1 or 2 min of the polystyrene calibration. Small molecules of mass less than 1000 units lay on or near to the polystyrene calibration lines, with a shift to late elution for the smallest molecules. This shift may be caused by the interaction with the column packing. A sample has been examined by analytical size exclusion chromatography, which was calibrated using polystyrene and polymethylmethacrylate standards. Molecular mass (MM) distributions of the sample have been examined in terms of these calibrations. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: size exclusion chromatography; calibration; coal-derived materials; MASS-SPECTROMETRY; 1-METHYL-2-PYRROLIDINONE; MATRIX; Chemistry